Attachment style and its impact on connection to God in individuals with brain injury: behavioral and lesion-based findings - Cohen-Zimerman, Shira; Cristofori, Irene; McNamara, Patrick; Krueger, Frank; Gordon, Barry; Grafman, Jordan (Frontiers in Neurology, 2025)
Attachment style shapes one's connections with important figures in their life. One such unique relationship is the connection to God (CTG), which may be shaped by attachment style. Stronger CTG has been associated with secure attachment, yet the neural mechanisms underlying this relationship remain unclear. While previous research has implicated the prefrontal cortex (PFC) in CTG, findings have been mixed and may depend on attachment style—an idea that has yet to be directly tested. This study aimed to (1) examine whether individuals with a secure attachment style report higher levels of CTG compared to those with a non-secure attachment style, and (2) identify the brain regions associated with CTG in individuals with secure vs. non-secure attachment. We assessed attachment style and CTG in a sample of male combat veterans (N = 150), the majority of whom had focal traumatic brain injuries (pTBI; N = 119). Brain imaging (CT scans) was also obtained. Behaviorally, after controlling for age, years of education, and brain volume loss, individuals with a secure attachment style reported stronger CTG. Voxel-based lesion-symptom mapping revealed that damage to the right orbitofrontal cortex was associated with stronger CTG in individuals with secure—but not insecure—attachment. These findings suggest that attachment style shapes CTG at both behavioral and neural levels. Moreover, they highlight the potential role of attachment style in TBI recovery, offering insights that could inform spiritually integrated therapeutic interventions and support strategies.